Determination of areas for surface refractivity variation analysis over Quebec - Bettouche, Yamina (2020)
For the aim of surface refractivity analysis, the overall territory of Quebec has been divided in a desired number of areas from North to South using clustering analysis. The meteorological data used in the analysis are collected from 50 stations located in various climatic regions over Quebec for the year 2013. It is found that the best input data for the identification of areas is the water vapour pressure. The results show that the surface refractivity increase from North to South and the maximum values for all areas are observed in July or in August. However, the variation of the surface refractivity remains in a relatively small interval in comparison to the variation observed in some tropical countries, particularly Nigeria.